Effects of the Public Sector downsizing on Social Security and public finance - Ioannis Vogiatzis; Costas Siriopoulos; Nikolaos Frangos (SPOUDAI - Journal of Economics and Business, 2014)
This paper presents the results of the actuarial valuation method Projected Unit Credit ("benefits/years of service") in order to assess the effects of the public sector downsizing on real economy and social security in Greece, using a prototype data set. We found a social security loss of about 1.3 bn. exteuro, and the effect on the GDP is estimated -13.6 bn. exteuro (or -7%). We also report a decrease in the direct income by 6.1 bn. exteuro.
Keywords: C58; H55; 330; Projected Unit Credit Method; Public Sector Downsizing; Pensions; Social Security